Ocular Onset of Paraneoplastic Pemphigus Presenting as Hyperemic Conjunctivitis and Massive Bilateral Eyelid Ulceration: A Case Report and Literature Review. (17th February 2018) - Piscopo, Raffaele; Romano, Mary; Maria, Alessandra Di; Vinciguerra, Riccardo; Vinciguerra, Paolo
ABSTRACT: Introduction : Paraneoplastic clinical signs are characterized by a large and heterogeneous variety of manifestations due to several possible underlying neoplasms. Paraneoplastic pemphigus (PNP) is a particular paraneoplastic variety that usually primarily affects the dermic and/or oral mucosa and is characterized by a high rate of mortality (90%). Therefore, it is important to recognize its possible signs early. This report describes a case of ocular paraneoplastic pemphigus (PNP) presenting with recalcitrant eyelid ulceration and hyperemic conjunctivitis caused by an undiagnosed prostate cancer. Methods : A 77-year-old man was admitted to our department because of recalcitrant hyperemic conjunctivitis in both eyes, complicated with large ulceration of both upper eyelids in spite of topical therapy. After 3 weeks, oral mucositis and bullous dermatitis on the chest and arms developed. Results : Complete slit lamp ocular study, conjunctival swabs, routine hematologic tests, serum neoplasm markers, indirect immunofluorescence study, immunoblotting, and oral mucose biopsy with direct immunofluorescence were performed under the hypothesis of a paraneoplastic sign. Total body computed tomography scan and ultrasound-guided needle prostate biopsy completed the diagnostic process and confirmed the diagnosis of prostate PNP. Complete remission of ocular clinical signs was achieved by treatment of the prostate malignancy with systemic immunosuppressive therapy and chemotherapy.